School of History - V. I. Ukolova (Vestnik MGIMO-Universiteta)
The current international processes and events, world politics at the beginning of the 21 century have once again clearly demonstrated that their meaning often emerges through the historical context without which the understanding of what is happening is hardly possible. Rector of MGIMO A.V. Torkunov in his talk on International relations as an educational discipline remarked that "as for sciences the basis of professionalism is mathematical skills and competencies, for international relations such a basis is history". Historical disciplines are taught at MGIMO from the very start of education process. MGIMO is one of the leading centers of research in the fields of history, political sciences and humanities. Here, in different years academics E.V. Tarle, L.N. Ivanov, V.G. Trukhanovskiy, A.L. Narochnitskiy and other prominent scholars and historians taught. Historical School of MGIMO has united important areas of historical science: the history of political processes in the twentieth century, modern history, the history of international relations and diplomacy, historical regional studies and cultural studies, oriental, philosophy and theory of history. The best traditions of the MGIMO historical school incorporated by its founders, make the foundation of its development at present. In 1992, the Department of MGIMO world and national history was established. The principle innovation was the combination of two components - historical education and historical science. This made it possible to present the story of Russia as an important part of the world history, opened up prospects for the implementation of comparative history, the synthesis of specific historical approaches and generalized global vision of civilization and human development. The historical school has realised a number of research projects, including "Alexander Nevsky" and the multi-volume "Great Victory", the work continues on a research project "Russia in the Modern World", and on a project "Synchronous History", etc.